ANALYSIS OF THE IMPLEMENTATION OF QUALITY CONTROL DEFECT PRODUCT IN SUGAR PRODUCTION OF PT SINERGI GULA NUSANTARA – PG GLENMORE, BANYUWANGI REGENCY - Sari, Dinda Puspa; Setyowati, Trias; Hafidzi, Achmad Hasan (Universitas Muhammadiyah Tangerang, 2024)
This research explores the causes of defects (reprocessing) in sugar production at PT Sinergi Gula Nusantara using a fishbone diagram approach. The critical factors identified include the lack of discipline and accuracy of employees (human factors), old and damage-prone machines (machine factors), unfavorable working environment conditions, such as hot air temperature and machine noise (work environment factors), and the absence of product standards in the winnowing process (work method factors). This study describes the implications of each factor on the quality of sugar products, proposes improvement solutions, and emphasizes the importance of increased discipline, machine maintenance, improved work environment conditions, and the establishment of product standards to increase the efficiency and effectiveness of sugar production in the company. The results of this study provide a holistic view of the dynamics of sugar production.